КƏМЕЛЕТКЕ ТОЛМАҒАНДАРДЫҢ ҚЫЛМЫСТЫҚ ЖАУАПКЕРШІЛІГІ (Journal of actual problems of jurisprudence, 2019)
The problem of the responsibility of the underage people for the violation of the law plays the main role in the crime control.